A Bibliometric Analysis of Nepal-India Relations: Mapping the Scholarly Discourse (2010-2025) - Dahal, Bal Krishna (NPRC Journal of Multidisciplinary Research, 2025)
Background: The bilateral relationship between Nepal and India, characterized by deep socio-cultural ties, political complexity, and economic interdependence, has been the subject of extensive qualitative scholarly inquiry. However, the existing literature remains fragmented, focusing on isolated case studies and lacking a macro-level synthesis of the field’s intellectual structure and evolution. Objectives: This study aims to fill this gap by conducting a comprehensive bibliometric analysis to systematically map and analyze the scholarly discourse on Nepal-India relations published between 2010 and 2025. It seeks to delineate key research themes, identify major contributors and their collaborative networks, and assess the field’s impact and intellectual trajectories. Methods: A systematic bibliometric approach was employed. Data for 26 relevant peer-reviewed articles were retrieved from the dimensions.ai database. Quantitative analysis was performed to examine publication trends, citation impact, and the contributions of countries and organizations. Network visualization was conducted using VOSviewer software to map intellectual linkages. Findings: The analysis reveals a significant increase in scholarly output post-2016, indicating growing academic interest. While a high proportion (65.38%) of publications achieve academic recognition, the field is marked by structural fragmentation. Research is dominated by Nepali institutions, particularly Tribhuvan University, but exhibits a critical lack of international and inter-organizational collaboration. The dissemination of knowledge is decentralized across numerous journals, and the intellectual discourse is siloed, with limited cross-journal citation dialogue. Key themes identified include the duality of cooperation and conflict, water resource governance, border disputes, and foreign policy strategy. Conclusion: The study concludes that while research on Nepal-India relations is active and impactful, it is constrained by significant isolation and a lack of a cohesive academic network. The findings underscore the need for greater international collaboration and more integrated scholarly communication to advance a cumulative and holistic understanding of this critical bilateral relationship. Novelty: This study provides the first systematic, quantitative bibliometric review of the Nepal-India relations literature, offering a novel, macro-level perspective on the field’s evolution, intellectual structure, and collaborative dynamics, which have previously been unexplored.